2016
DOI: 10.20956/halrev.v2i3.701
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Strengthening the Right to Sustainable Groundwater (Assessing Model Policy in Bandar Lampung City)

Abstract: Implementation of sustainable development related to the management of groundwater resources in the area can be realized with the establishment of a policy which is inseparable from the values prevailing in the society. The formation of ground water resources management policies is not only technically partial, but must also be comprehensive-holistic. Groundwater management activities include the conservation and utilization of groundwater organized to realize the sustainability and continuity of availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Groundwater management in coastal areas is an environmental issue that requires a holistic approach. The limited ability to provide clean water and the weak application of regulations are factors for uncontrolled groundwater extraction on the coast of Bandar Lampung [21]. Indications of seawater intrusion have been identified on the coast of Bandar Lampung based on gravity and geoelectric data [22].…”
Section: Applied Environmental Researchmentioning
confidence: 99%
“…Groundwater management in coastal areas is an environmental issue that requires a holistic approach. The limited ability to provide clean water and the weak application of regulations are factors for uncontrolled groundwater extraction on the coast of Bandar Lampung [21]. Indications of seawater intrusion have been identified on the coast of Bandar Lampung based on gravity and geoelectric data [22].…”
Section: Applied Environmental Researchmentioning
confidence: 99%
“…As reported by the East Kalimantan Mining Advocacy Network (MAN), the continued operation of 151 illegal mines in four regions of East Kalimantan is a cause for concern, leading to growing indifference among local governments as the issuance of mining permits is centralized by the Central Government. 15 Erina Pane and Adam Muhammad Yanis in their previous research Reconstruction of Fair Mining Policies in Lampung Province revealed that the management of mineral and coal mining must be supported by policies that are environmentally sound, because mining activities have the possibility of uncontrolled environmental damage while efforts that can be made by local governments is to pay attention to permits for managers, provide guidance, supervision, so that mining activities can be controlled and not damage the environment 16 . Mohammad Jamin and friends while in his research The Impact of Indonesian Mining Industry Regulations on the Protection of Indigenous Peoples revealed There are two kinds of law rule state conceptions.…”
Section: Introductionmentioning
confidence: 99%